Variability of Jupiter's Synchrotron Radiation: Goldstone Apple Valley Radio Telescope (GAVRT) Observations -II. (1st August 2022) - Matuszewska, K.; Velusamy, T.; Adumitroaie, V.; Arballo, J.; Dorcey, R.; Han, S.; Klopping, E.; Kreuser-Jenkins, N.; Levin, S.; Santos-Costa, D.
Abstract: Jupiter's decimeter-wavelength flux density is dominated by synchrotron emission from magnetically trapped ∼5–50 MeV electrons in the radiation belts. Synchrotron radio emission remains the most useful diagnostic of the radiation belts, and a global picture is provided by ground-based observations. Monitoring of the long-term variations of Jupiter's Synchrotron Radiation (JSR) flux density is crucial to understanding its relationship with the solar wind. The GAVRT (Goldstone-Apple Valley Radio Telescope) program operates two retired Deep Space Network (DSN) antennas, and as part of their K-12 program and Juno support, GAVRT has been collecting data to monitor JSR radio emission at 2280 MHz (13 cm wavelength). We present new results from 2019 August to 2021 December GAVRT monitoring observations. As viewed from Earth the JSR varies systematically (by about 10%) with Jupiter's 9.9 hr rotation period, and our observations were typically much shorter than 9.9 hr. To estimate the daily flux density of JSR, we took advantage of recent progress in modeling the radiation belt, scaling individual observations by the predicted relative variation due to Jupiter's rotation as viewed from Earth. We discuss the JSR variability from 2015 to 2021, combining our results with previous GAVRT data. Our new results show a marked decrease (∼1 Jy) in JSR flux density between 2018 and 2021, while earlier observations showed an increase from 2015 to 2018. These results are remarkably consistent with long-term variability shown by the simulations of Han et al. based on models driven by the solar wind ram pressure.